CENTRAL SENSITIZATION IN CHRONIC PAIN: NEUROPHYSIOLOGICAL MECHANISMS AND CLINICAL IMPLICATIONS - Jakub Przerwa (International Journal of Innovative Technologies in Social Science, 2025)
The definition of central sensitization encompasses enhanced processing and transmission of neural impulses within the central nervous system, ultimately leading to increased pain sensitivity. It is a key mechanism contributing to the development of chronic pain. This phenomenon is of great clinical relevance and plays a role in such conditions as migraine, chronic low back pain, fibromyalgia, and irritable bowel syndrome. The main aim of this review is to present the mechanisms underlying central sensitization, diagnostic methods, and potential therapeutic interventions in patients with chronic pain. Diagnostic tools that allow for the identification of patients with sensitization-related pain, as well as key neurophysiological mechanisms necessary for maintaining central sensitization, are also discussed. Future research should focus on developing therapeutic protocols targeting CS, identifying sensitization biomarkers, and improving diagnostic precision.